2020
DOI: 10.1093/eurpub/ckaa112
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-HEV antibodies and RNA of HEV in pigs from a hyperendemic Italian region with high human seroprevalence

Abstract: Background Pigs are considered the main reservoir of genotypes 3 and 4 of hepatitis E virus (HEV), which is the major cause of acute hepatitis of viral origin in humans worldwide. An increasing number of autochthonous HEV infections have been observed in recent years in industrialized countries, most likely as a result of zoonotic transmission through the consumption of raw or undercooked meat products. Methods Two hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
5
2
Order By: Relevance
“…In the Abruzzo region, where 26 analyzed farms were located, small sized herds are present mainly for the Italian or local market. Abruzzo is an HEV genotype 3 hyperendemic area for humans (29) but this does not correspond either to a higher percentage of positive HEV herds (in this study) or to higher percentage of positive animals at slaughterhouse, as observed in a recent study conducted by HEV detection in liver on pigs at slaughter (40). The link between high seroprevalence in humans in Abruzzo and the consumption of raw pork liver (e.g., sausages) has been confirmed by epidemiological data (29).…”
Section: Discussioncontrasting
confidence: 73%
“…In the Abruzzo region, where 26 analyzed farms were located, small sized herds are present mainly for the Italian or local market. Abruzzo is an HEV genotype 3 hyperendemic area for humans (29) but this does not correspond either to a higher percentage of positive HEV herds (in this study) or to higher percentage of positive animals at slaughterhouse, as observed in a recent study conducted by HEV detection in liver on pigs at slaughter (40). The link between high seroprevalence in humans in Abruzzo and the consumption of raw pork liver (e.g., sausages) has been confirmed by epidemiological data (29).…”
Section: Discussioncontrasting
confidence: 73%
“…Among them, the hepatitis E virus (HEV) is regarded as an emerging public health concern [60]. Hepatitis E virus belongs to the Hepeviridae family, genus Paslahepevirus [61][62][63], and causes hepatitis in humans by consumption of undercooked meat and meat products in industrialized countries [64].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, anti-HEV IgG seroprevalence reached 66% in slaughterhouse staff, 51% in pig-farmers, and 38% in pork meat vendors [ 46 ] and those who had exposure to pigs or pork meat had high chances of HEV infection when compared with unexposed individuals [ 46 ]. A study from Abruzzo, Italy, a reportedly hyperendemic region having the highest HEV seroprevalence in humans, out of 233 blood samples collected from different local pig slaughterhouses between 87.3% and 100% of serum samples were found positive for anti-HEV antibodies (IgG), such high seroprevalence in pigs suggests the intense circulation of HEV in the region [ 82 ]. Previously published studies showed that pigs successively receive HEV infection on farms, where a higher prevalence was found among older pigs [ 26 , 83 , 84 ].…”
Section: Hev Infection In Livestock In Particular Pigsmentioning
confidence: 99%